PENGARUH INTERVENSI HUKUM ADAT MINANGKABAU TERHADAP PRINSIP DAN PRAKTIK HUKUM ISLAM - Sidiq Siadio; Endri Yenti (Institut Agama Islam Negeri Batusangkar, 2023)
This study aims to analyze the influence of Minangkabau customary law intervention on the principles and practices of Islamic law. Minangkabau customary law has a long history and is an integral part of the strong cultural heritage of the Minangkabau community. On the other hand, Islamic law is also the majority religion believed by the Minangkabau people. This research adopts a qualitative approach with a case study method to gain a deep understanding of the interaction between Minangkabau customary law and Islamic law in terms of principles and legal practices. Data were collected through interviews, observations, and analysis of relevant documents. The findings of the study indicate that Minangkabau customary law intervention has a significant influence on the principles and practices of Islamic law. Minangkabau customary law often functions as a social norm that affects decision-making in Islamic legal cases. Principles of customary law, such as adat istiadat (customary traditions), adat basandi syarak (custom based on Islamic law), syarak basandi kitabullah (Islamic law based on the Quran), and adat basandi adat (custom based on customs), often play a vital role in resolving legal cases. However, there are also potential conflicts between Minangkabau customary law and Islamic law in some cases. Certain customary law practices that contradict Islamic principles, such as unequal inheritance between men and women, have sparked debates within the Minangkabau community